Legal services today and in the future: how is changing the job of a lawyer? - Stankutė, Martyna (Vilnius University Open Series, 2020)
This article is analyzing law and information technologies scientists works, were law technologies and their realization in lawyer work implies also its benefits and disadvantages through the following future. To rely on the linguistic and analysis method in this article explains the way legal technologies work in different fields, modifying individual legal services actions. Analyzing innovative technology tools and showing their practical integration and applicability trough examples. An analysis of the relationship between law technology and a lawyer today has shown what the technology gaps are and what features a lawyer will need in the future. Technologies being an innovative creations of a human and working in virtual field can‘t function without humans, so it could emerge cybernetic attacks risks. To that point helping tools would be automatic, yet it will remain an aid tool. Laws and decision making would be left for human being, however, lawyers should maintain abilities that would let them successfully integrate with modern technology changes.
Keywords: none